Chemoselective α, β‐Dehydrogenation of Saturated Amides. Issue 2 (7th December 2018) - Teskey, Christopher J.; Adler, Pauline; Gonçalves, Carlos R.; Maulide, Nuno
Abstract: We report a method for the selective α, β‐dehydrogenation of amides in the presence of other carbonyl moieties under mild conditions. Our strategy relies on electrophilic activation coupled to in situ selective selenium‐mediated dehydrogenation. The α, β‐unsaturated products were obtained in moderate to excellent yields, and their synthetic versatility was demonstrated by a range of transformations. Mechanistic experiments suggest formation of an electrophilic Se IV species. Abstract : Make it a double : A method for the selective α, β‐dehydrogenation of amides in the presence of other carbonyl moieties under mild conditions has been developed. This strategy relies on electrophilic activation coupled to in situ selective selenium‐mediated dehydrogenation. Mechanistic experiments suggest formation of an electrophilic Se IV species.